Screening for cervical cancer (By VIA Test) among selected garments worker in Chattogram, Bangladesh - Shirin, Fahmida; Chowdhury, Fahmida Islam; Sultana, Munawar; Chowdhury, Sahnaz Jahan; Sultana, Nahid; Karim, Tanjila; Ara, Sarwat; Ferdous, Jannatul; Akter, Shamima; Shiblee, S. A.; Ahmed, Mohsin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Bangladesh is a densely populated country of South East Asia with low resource setting where cervical cancer is the 2nd leading cause of female cancer. In more than 80% cases are diagnosed at advanced and inoperable stage. Regarding socio demographic context of this country VIA has been introduced as a screening method for cervical cancer which is most simple, cost effective, and acceptable test for all women. In Bangladesh among 3 million garment workers more than 80% are women. The objective of this study was to identify prevalence of VIA positive cases among garment workers. So that it can reduce the incidence of cervical cancer in Bangladesh. Methods: It was a cross–sectional observational study conducted in some selected garment factories in Chattogram city of Bangladesh from January 2021 to July 2021, where we enrolled 534 female workers for VIA test. Results: Among all the respondents 56% were 30 years or younger, 38% were aged between 31 to 40 years. Among 534 participants, 44.9% completed primary education, 37.3% were smoker and 34.5% had their children at early age. Majority (86.7%) had excessive whitish discharge. Post coital bleeding and irregular bleeding was 2.6% and 2.2% respectively. Considering awareness, 61.8% had idea about cervical cancer, only 1.1% had undergone VIA test in the past. In our study we found 2.4% of participants were VIA positive cases. Conclusions: It is important to include the garment workers, while making public health policies and implementation of cervical cancer control program.